Analisis Kesalahan Siswa dalam Menyelesaikan Soal Identitas Trigonometri di Kelas XI MIA SMAK St. Dominikus Tambolaka - Ina, Mitalia Tamo; Lubur, Dorothea Novia Ludo (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine student errors and the causes of student errors in solving trigonometric identity problems in class XI MIA SMAK St. Dominic Tambolaka. The type of research used is qualitative descriptive. The subjects of the study were 18 class XI MIA students at SMAK St. Dominikus Tambolaka. Data collection techniques use written tests and interviews. The results showed the percentage of errors made by students in solving math problems related to trigonometric identity. The causes of student errors include rushing to read math problems, not having the ability to focus attention on learning, not mastering trigonometric identity material, not understanding the formula that should be used, not being careful in carrying out the calculation process, carelessly doing problems because of previous mistakes, and rushing in working on the solving process.